Phase 1 Single‐ and Multiple‐Ascending‐Dose Randomized Studies of the Safety, Pharmacokinetics, and Pharmacodynamics of AG‐348, a First‐in‐Class Allosteric Activator of Pyruvate Kinase R, in Healthy Volunteers. Issue 2 (9th August 2018) - Yang, Hua; Merica, Elizabeth; Chen, Yue; Cohen, Marvin; Goldwater, Ronald; Kosinski, Penelope A.; Kung, Charles; Yuan, Zheng (Jason); Silverman, Lee; Goldwasser, Meredith; Silver, Bruce A.; Agresta, Sam; et al.
Abstract: Pyruvate kinase deficiency is a chronic hemolytic anemia caused by mutations in PK‐R, a key glycolytic enzyme in erythrocytes. These 2 phase 1 randomized, placebo‐controlled, double‐blind healthy‐volunteer studies assessed the safety, tolerability, and pharmacokinetics/pharmacodynamics of AG‐348, a first‐in‐class allosteric PK‐R activator. Twelve sequential cohorts were randomized 2:6 to receive oral placebo or AG‐348, respectively, as a single dose (30‐2500 mg) in the single‐ascending‐dose (SAD) study (ClinicalTrials.gov: NCT02108106) or 15‐700 mg every 12 hours or 120 mg every 24 hours, for 14 days in the multiple‐ascending‐dose (MAD) study (ClinicalTrials.gov: NCT02149966). All 48 subjects completed the fasted SAD part; 44 of 48 completed the MAD (2 discontinued because of adverse events [AEs], 2 withdrew consent). The most common treatment‐related AEs in AG‐348‐treated subjects were headache (16.7% [SAD] and 13.9% [MAD]) and nausea (13.9%, both studies). AE frequency increased at AG‐348 doses ≥ 700 mg (SAD) and at 700 mg every 12 hours (MAD); 1 grade ≥ 3 AE occurred in the latter cohort. Pharmacokinetics were favorable with low variability. Dose‐dependent changes in blood glycolytic intermediates consistent with glycolytic pathway activation were observed at all MAD doses, supporting future trials investigating the potential of AG‐348 for treating PK deficiency or other anemias.